THE INFLUENCE OF E SERVICE QUALITY, ONLINE CUSTOMER REVIEWS AND PRICE PERCEPTION ON DECISIONS TO PURCHASE FASHION PRODUCTS ON SHOOPE - Muhammad Athallah Syahrul Ramadhan; Endah Budiarti (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research aims to analyze the influence of E Service Quality, Online Customer Reviews and Price Perceptions on Purchase Decisions for fashion products at Shope. The data obtained through the questionnaire that was distributed was 100 respondents who had bought fashion products on Shope. The method used to test the analysis of this research is Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) mediation test tool which is used to test the relationship between variables in the conceptual framework that has been formulated